Evaluation of micronuclei in oral mucosa of individuals exposed to ionizing radiation: a pilot study from Celaya, México - Nicolas Padilla-Raygoza; María del Rocio Adame Gutiérrez; Itza Zelene Moreno Martínez; Vicente Beltran-Campos; Silvia del Carmen Delgado-Sandoval; Maria de Lourdes Garcia-Campos; Modesto Antonio Sosa-Aquino; Teodoro Cordova-Fraga; Rafael Guzman-Cabrera (University Library System, University of Pittsburgh, 2019)
Introduction: Occupational exposure to ionizing radiation can potentially lead to adverse health effects, including cancer and genetic defects. Genetic damage caused by radiation can be detected if micronuclei are observed. The objective of this pilot study was to detect the presence of micronuclei in cells of the oral mucosa in inidividuals occupationally exposed to ionizing radiation. Methods:  We implemented a pilot case-control study in which we compared oral mucosa micronuclei in 30 medical and nursing personnel in radiology centers in Celaya, Mexico, with 30 volunteers not exposed to ionizing radiation recruited from a public University. The oral mucosa was brushed and the amount of micronuclei was quantified. Chi-square test or t-test for two proportions were used to compared ionizing radiation and genetic damage between exposed and non-exposed groups. Results: The exposed group had an average of 5.37 ± 3.49 micronuclei and the non-exposed had 0.37 ± 0.61 (P<0.01). In the exposed group, 90% of participants exhibited genetic damage compared to 6.67% in the unexposed group (P<0.05). Conclusion: In this pilot study, medical and nursing staff from radiology centers presented with higher genetic damage compared to control group. Further studies are needed to identify the prevalence of genetic damage due to occupational radiation exposure in Mexico.